A Protocol for Transverse Cardiac Slicing and Optical Mapping in Murine Heart - He, S.; Wen, Q.; O’Shea, C.; Mu-u-min, R.; Kou, K.; Grassam-Rowe, A.; Liu, Y.; Fan, Z.; Tan, X.; Ou, X.; Camelliti, P.; Pavlovic, D.; et al. (Frontiers in Physiology, 2019)
Thin living tissue slices have recently emerged as a new tissue model for cardiac electrophysiological research. In the present protocol, we describe a detailed mouse heart transverse slicing and optical imaging methodology. The use of this technology for high-throughput optical imaging allows studying cellular electrophysiology of murine heart in an organotypic pseudo two-dimensional ventricular tissue model. Transverse slices are cut at right angles to the long axis of the heart, permitting for robust interrogation of transmembrane potential (Vm) and calcium transients (CaT) throughout the entire heart with exceptional regional precision. This approach enables the use of a series of slices prepared from the ventricles to measure Vm and CaT with high temporal and spatial resolution, allowing i) comparison of successive slices which form a stack representing the original geometry of the heart; ii) profiling of transmural and regional gradients in Vm and CaT in the ventricle; iii) characterization of transmural and regional profiles of action potential and CaT alternans. Thus, the protocol described here provides a powerful platform for innovative research on heterogeneity in the heart. It can be also combined with optogenetic technology to carry out optogenetic light stimulation aiding studies of cellular Vm and CaT in a cell type specific manner.